Quality and psychosocial factors influencing purchase of orange‐fleshed sweet potato bread - Okello, J.J.; Shiundu, F.M.; Mwende, J.; Lagerkvist, Carl Johan; Nyikal, R.A.; Muoki, Penina Ngusye; Mburu, J.; Low, Jan W.; Hareau, Guy; Heck, S. (Wiley, 2021)
This 2018 study, conducted in six Tusky's supermarkets in Nairobi, Kenya, combined the Just‐About‐Right, Penalty and Mean‐End‐Chain analyses to examine the quality and psychosocial factors influencing the purchase of a novel bread made from orange‐fleshed sweet potato (OFSP), a biofortified crop, focusing on sixty‐one male and eighty female urban OFSP bread buyers recruited at point of purchase. It finds that sensory and psychosocial factors drive purchasing decisions and that some of the bread's sensory characteristics are misaligned with consumers' expectations. It also finds that women and men’s evaluations of the bread's characteristics are different, as are their motivations for purchase. However, good sensory attributes and the knowledge of the bread's nutritional value were key drivers. Some misaligned characteristics reveal levers for the reformulation of the bread and present opportunities for segmenting the market. Several other implications of the findings for policy and future improvement of the bread are discussed.